Pengaruh Penggunaan Media Buku Cerita Bergambar Terhadap Minat Baca Siswa Sekolah Dasar Kelas V di Desa Cigondewah Hilir - Henita Komariah; Dheni Harmaen; Arifin Ahmad (FKIP, Universitas Palangka Raya, 2024)
This research is motivated by the lack of public attention to reading interest so that it affects learning outcomes as a form of the quality of Indonesian education. One of the main factors to advance the Indonesian state is the quality of its population which is seen in the quality of Indonesian education, but in reality Indonesia is at a low level from other Southeast Asian countries, therefore the importance of familiarizing students from an early age to foster interest in reading by using interesting media, one of which is with picture storybooks. Thus this study was conducted to determine the effect of picture storybook media on students' reading interest. The approach used in this research is a non-experimental quantitatif aproach to a Survey Research Design. Data collection techniques through the distribution of questionnaires (questionnaires) and observation sheets. The sample used was purposive sampling because the total number of grade V students in Cigondewah Hilir Village exceeded 100 students. from in the process of the independent variable questionnaire, a score of 77.4% was obtained in the good category, reinforced by the results of observation sheet data for two meetings there was an increase in scores, namely at the first meeting of 6072 and the second meeting of 6199. Then the questionnaire processing on the dependent variable shows a percentage of 81.8% reading interest which is classified as very high. search on these findings Indicate that the independent variable (the use of picture storybook media) affects the dependent variable (student reading interest) by 60% and 40% is influenced by other factors. Based on the explanation above, it can be concluded that there is an effect of using picture storybook media on the reading interest of fifth grade elementary school students in Cigondewah Hilir Village, Margaasih District, Bandung Regency.